Authentication Revolution using Bring Your Own Identity (International Journal of Scientific Research and Management (IJSRM), 2017)
With the growing acceptance of cloud-based services, it is becoming less important where an identity access management (IAM) system actually resides. Proponents of BYOID maintain that traditional identity provisioning is no longer necessary and allowing a third party to assume the security, privacy and compliance burdens associated with IAM reduces administrative overhead, simplifies data management and lowers storage costs. Adversaries warn that BYOID has too many risks, including the potential for compromised identities and identity theft. In the enterprise, BYOID may be called identity as a service (IDaaS). IDaaS for the enterprise is typically purchased as a subscription-based managed service that provides subscribers with role-based access to specific applications or virtualized desktops through a secure portal.